2002
DOI: 10.1046/j.1365-2818.2002.01078.x
|View full text |Cite
|
Sign up to set email alerts
|

Mapping cholesteryl ester analogue uptake and intracellular flow in Paramecium by confocal fluorescence microscopy

Abstract: SummaryIn Paramecium primaurelia the uptake and intracellular flow of cholesteryl ester was studied by fluorescence confocal laser scanning optical microscopy and by the fluorescent analogue cholesteryl-BODIPY ® FL C 12 (BODIPY-CE). The BODIPY FL fluorophore has the characteristic of emitting green fluorescence, which is red-shifted as the probe concentrates. In cells incubated with 25 µ m BODIPY-CE for 30 s, fluorescence is found in vesicles located around the cytopharynx in the posterior half of the cell. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
2
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 50 publications
(54 reference statements)
3
2
0
Order By: Relevance
“…When NAs were incubated on the transwells at 4 °C, no detectable passage of the BODIPY dye could be observed (Figure B), suggesting an energy-dependent transcytosis mechanism across the cell monolayer. Finally, incubating the cells with the BODIPY-FL probe alone resulted in a reduced passage of the dye, comparatively to BODIPY-embedded NAs (Supporting Information, Figure 20), which was consistent with the storage of the free fluorescent probe into lipidic droplets inside the cell cytoplasm . More importantly, this observation demonstrated that the NAs triggered the transcytosis of the BODIPY dye.…”
Section: Resultssupporting
confidence: 65%
“…When NAs were incubated on the transwells at 4 °C, no detectable passage of the BODIPY dye could be observed (Figure B), suggesting an energy-dependent transcytosis mechanism across the cell monolayer. Finally, incubating the cells with the BODIPY-FL probe alone resulted in a reduced passage of the dye, comparatively to BODIPY-embedded NAs (Supporting Information, Figure 20), which was consistent with the storage of the free fluorescent probe into lipidic droplets inside the cell cytoplasm . More importantly, this observation demonstrated that the NAs triggered the transcytosis of the BODIPY dye.…”
Section: Resultssupporting
confidence: 65%
“…Figure 5A shows co-localization between fluorescent E. coli and bodipy-cholesterol, suggesting that cholesterol is taken up via phagocytosis. These results are in accordance with previous experiments carried out in the ciliate Paramecium [27].…”
Section: Figsupporting
confidence: 94%
“…The appearance of red-stained particles in the ciliate (a well-known bacteriovorus organism) would confirm the use of this pathway. These results are in accordance with previous experiments carried out in the ciliate Paramecium [27]. These results are in accordance with previous experiments carried out in the ciliate Paramecium [27].…”
Section: Intracellular Localization Of Substrates and Enzymessupporting
confidence: 93%
“…Endocytosis via coated pits was tested as indicated by Ramoino et al (46). Briefly, phagocytosis was inhibited by trifluoperazine (2.5 g/ml; Sigma-Aldrich, St. Louis, MO), and internalization of endocytic vesicles from the cell surface was followed with wheat germ agglutinin labeled with AlexaFluo-488 (Sigma-Aldrich, St. Louis, MO) for fluorescence analysis in a Zeiss Axiovert 100TV.…”
Section: Methodsmentioning
confidence: 99%